Exaggerated postural sway improves orthostatic cardiovascular and cerebrovascular control - Williams, Erin L.; Hockin, Brooke C. D.; Heeney, Natalie D.; Elabd, Karam; Chong, Helen; Blaber, Andrew P.; Robinovitch, Stephen N.; Parsons, Iain T.; Claydon, Victoria E. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Healthy individuals with poor cardiovascular control, but who do not experience syncope (fainting), adopt an innate strategy of increased leg movement in the form of postural sway that is thought to counter orthostatic (gravitational) stress on the cardiovascular system. However, the direct effect of sway on cardiovascular hemodynamics and cerebral perfusion is unknown. If sway produces meaningful cardiovascular responses, it could be exploited clinically to prevent an imminent faint. Methods Twenty healthy adults were instrumented with cardiovascular (finger plethysmography, echocardiography, electrocardiogram) and cerebrovascular (transcranial Doppler) monitoring. Following supine rest, participants performed a baseline stand (BL) on a force platform, followed by three trials of exaggerated sway (anterior-posterior, AP; mediolateral, ML; square, SQ) in a randomized order. Results All exaggerated postural sway conditions improved systolic arterial pressure (SAP, p = 0.001) responses, while blunting orthostatic reductions in stroke volume (SV, p < 0.01) and cerebral blood flow (CBFv, p < 0.05) compared to BL. Markers of sympathetic activation (power of low-frequency oscillations in SAP, p < 0.001) and maximum transvalvular flow velocity (p < 0.001) were reduced during exaggerated sway conditions. Responses were dose-dependent, with improvements in SAP (p < 0.001), SV (p < 0.001) and CBFv (p = 0.009) all positively correlated with total sway path length. Coherence between postural movements and SAP (p < 0.001), SV (p < 0.001) and CBFv (p = 0.003) also improved during exaggerated sway. Discussion Exaggerated sway improves cardiovascular and cerebrovascular control and may supplement cardiovascular reflex responses to orthostatic stress. This movement provides a simple means to boost orthostatic cardiovascular control for individuals with syncope, or those with occupations that require prolonged motionless standing.